Platelet lysates-based hydrogels for the development of 3D models for bone cancer - Monteiro, Cátia Filipa Rodrigues (2020)
Cancer is the second-leading cause of death worldwide and regarding the bone-related cancers, osteosarcoma (OS) is the most common primary malignant tumor which is characterized by its high potential to metastasize, predominantly affecting children and adolescents. Despite the innumerable efforts towards the development of new anti-cancer therapies, several efficacious drug candidates identified in preclinical tests fail during clinical trials. Three-dimensional (3D) cell culture systems have been proposed as reliable in vitro platforms for tumor modelling in an attempt to closely reproduce the tumor pathophysiology and properly identify effective therapies. Human methacryloyl platelet lysates (PLMA)-based hydrogels were recently proposed as cost-effective and biologically relevant 3D in vitro platforms for human cell growth and proliferation. Therefore, the aim of this work was, in a first approach, to validate the PLMA hydrogels as reliable 3D platforms to support in vivo-like cell spheroid invasion mechanisms and subsequently explore that potential to establish humanized 3D mono- and co-culture OS invasion models for drug screening and validation. Spheroids of three tumor cell lines (MG-63, SaOS-2 and A549) and human bone marrow-derived mesenchymal stem cells (hBM-MSC) were embedded into PLMA hydrogels (three different concentrations), Matrigel and poly(ethylene glycol) diacrylate. PLMA hydrogels demonstrated to support the phenotypic heterogeneity of solid tumors and the acquisition of an in vivo-like cell polarity. Furthermore, these hydrogels perfectly recapitulated the cell invasiveness ability, demonstrating that invasion speed can be easily controlled through PLMA hydrogel stiffness. The co-culture of MG-63 spheroids with human osteoblasts and hBM-MSCs demonstrated that the crosstalk between tumor invading cells and stromal cells was truly recapitulated into PLMA hydrogels. A doxorubicin treatment in mono- and co-culture OS models clearly reflected the protective role of stromal cells in OS chemoresistance, exhibiting a drug response closest to in vivo. Overall, the results validated the humanized PLMA-based hydrogels as reliable 3D in vitro platforms to support an in vivo-like tumor morphology and invasiveness. Moreover, the complexity of the established co-culture OS model provided a more pathophysiological in vitro environment for screening and validation of anti-metastatic agents in order to predict patients’ response and expedite the availability of effective therapies.